Glioblastomas vs. Lymphomas: More Diagnostic Certainty by Using Susceptibility-Weighted Imaging (SWI) - Peters, S.; Knöß, N.; Wodarg, F.; Cnyrim, C.; Jansen, O. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: It can be difficult to differentiate glioblastomas from lymphomas using only standard MR images. There are references suggesting that it might be possible to differentiate these tumors using susceptibility-weighted imaging (SWI). The purpose of this study is to prove the diagnostic benefit using susceptibility-weighted images. Material and Methods: Three neuroradiologists tried to differentiate 4 histologically verified lymphomas from 11 glioblastomas in retrospect. They first viewed the conventional MR images and declared a diagnosis with a grade of certainty. Afterwards they additionally reviewed the susceptibility-weighted images. Results: Glioblastomas have a clearly higher grade of susceptibility signals than lymphomas. By additionally using susceptibility-weighted images, the radiologists determined the correct diagnosis in 82.2 % of the cases. Without susceptibility-weighted images, the diagnosis was correct in 75.5 % of the cases. The subjective gain of certainty was 16.5 %. If there were no intratumoral susceptibility signals (ITSS) (grade 1), the sensitivity for diagnosing a lymphoma was 70 % and the specificity was 100 %. The sensitivity for diagnosing a glioblastoma was 90.5 % and the specificity was 100 % if there was a high rate of intratumoral susceptibility signals (grade 3). Conclusion: Susceptibility-weighted images are an additional tool in clinical practice for determining the correct diagnosis. The differentiation between glioblastomas and lymphomas and the certainty of the determined diagnosis are better. Therefore, we recommend adding susceptibility-weighted imaging to the clinical MR tumor protocol.
Keywords: lymphoma; brain; MR imaging; astrocytoma